EFIKASI VAKSIN INAKTIF BIVALEN AVIAN INFLUENZA VIRUS SUBTIPE H5N1 (CLADE 2.1.3. DAN CLADE 2.3.2) DI INDONESIA - Dharmayanti, NLP Indi; Indriani, Risa (JURNAL BIOLOGI INDONESIA, 2015)
ABSTRACTStatus of avian influenza virus subtype H5N1 in Indonesia until 2014 is still endemic in poultry and recorded, there were two types clade of circulating H5N1 namely clade 2.1.3 and the new introduction of lade 2.3.2 since the end of 2012. Both of the clade of avian influenza viruses subtype H5N1 (clade 2.1.3 and 2.3.2) caused the the  AI vaccination program to control of AI in poultry needs to be evaluated.  In this study, we developed a bivalent AI vaccine (which contains clade 2.1.3 and 2.3.2 viruses as a seed vaccine) that   adapted with  the circulation of AI viruses in the field. Result of the study showed that the bivalent vaccine which developed in this study has good efficacy that was challanged with both of AI clade AI and proven to reduce shedding / viral contamination to the environment. It is expected that  the development of bivalent H5N1 vaccine will increase the effectiveness and efficacy of vaccination programs to control highly pathogenic avian influenza disease in Indonesia. Keywords : avian influenza virus, clade, vaccine, bivalent